Jeruju (Acanthus ilicifolius) Leaf Infusion Modulates Superoxide Dismutase (SOD) and Glutathione Peroxidase (GPx) Enzyme Activity in Streptozotocin-Nicotinamide (STZ-NA) Induced Diabetic Rats (Rattus norvegicus) - Chairina, Ade; Majdiyyah, Munifa; Afifah, Diana Nur; Syauqy, Ahmad (Media Publikasi Cendekia Indonesia, 2025)
Type 2 diabetes mellitus is a metabolic disorder marked by chronic hyperglycemia and oxidative stress, which can reduce the activity of antioxidant enzymes like Superoxide Dismutase (SOD) and Glutathione Peroxidase (GPx). Acanthus ilicifolius (jeruju) contains antioxidant compounds such as flavonoids and phenolics that may enhance these enzyme activities. Evaluate the effect of Acanthus ilicifolius leaf infusion on SOD and GPx activity in Wistar rats induced with type 2 diabetes using Streptozotocin-Nicotinamide (STZ-NA). The experimental design used a post-test only with five groups: normal control (no diabetes, standard feed), positive control (diabetes + metformin 45 mg/kgBW), negative control (diabetes without treatment), treatment group 1 (diabetes + metformin 45 mg/kgBW + jeruju infusion 1.2 ml/200gBW), and treatment group 2 (diabetes + metformin 45 mg/kgBW + jeruju infusion 2.4 ml/200gBW). Treatments were given daily for 30 days, and all rats had free access to food and water. At the end of the study, blood samples were collected to measure SOD and GPx activity using spectrophotometry. The combination of Acanthus ilicifolius infusion and metformin particularly at the 2.4 ml/200gBW dose, was associated with elevated SOD P2 treatment group (76.23 ± 3.65 U/mL; p = 0.000 (<0.05)) and GPx activities P2 (52.11 ± 0.76 U/mL; p = 0.000 (<0.05)) compared to the untreated diabetic group K- (SOD) (28.43 ± 3.17 U/mL) and K- (GPx)(24.18 ± 1.08 U/mL). These findings proves Acanthus ilicifolius infusion holds potential as an adjuvant therapy to mitigate oxidative stress in type 2 diabetes by enhancing SOD and GPx enzyme activities.